Aesthetics, Emotions, and the Use of Online Education Apps Post-COVID-19 Pandemic. (April 2022) - Sharma, Daneshwar; Alam, Mumtaz
The COVID-19 pandemic has forced governments all around the world to impose lockdowns. As schools were closed and the students could attend schools physically, online education apps were used by the students to continue their education. The purpose of the study was to analyze the students' intentions to use online education apps (OEAs) in the post-pandemic scenario. Purposive sampling was used to collect data from 327 first-time users of OEAs for their standard XII education. Various scales related to OEA's aesthetics, students' emotional response to OEAs, and the intentions to use OEAs in the post-pandemic scenario were used in the survey questionnaire. Correlations were analyzed to find answers to the research questions. The findings reflect that the aesthetics of OEA like the app design, graphics, structure, etc. significantly influence the emotional response and the intention of the students to use OEAs in the post-pandemic scenario. The emotional response of the students toward the OEAs, in itself, also influences the intention of the students to use OEAs in the post-pandemic scenario. When the students get pleasure, become excited, and feel in control of the app, their intention to use the OEAs in the post-pandemic scenario is positively influenced. The research adds to the literature related to OEAs, the aesthetics of OEAs, the emotional response to OEAs, and the intention to use OEAs. The OEA industry can use the finding to grow their consumer base in the post-pandemic scenario. The context of OEA and the results are original in nature.